2009
DOI: 10.1183/09031936.00145708
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cardiac autonomic control relates to disease severity in pulmonary hypertension

Abstract: Pulmonary arterial hypertension (PAH) results in chronic right heart failure, which is associated with an increase in sympathetic tone. This may adversely affect cardiac autonomic control. We investigated the changes in cardiac autonomic nervous activity in relation to disease severity in patients with PAH.In 48 ) and 41 controls, cardiac autonomic nervous activity was evaluated by measurement of heart rate variability (HRV) and baroreflex sensitivity. All patients underwent cardiopulmonary exercise testing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 37 publications
8
112
0
5
Order By: Relevance
“…Ventilation was slightly increased in CTEPH at rest and during exercise (15 (4-21) versus 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and 58 (29-78) versus 50 (29-82) L?min -1 ), but with no significant difference between the two groups. There were no significant differences between CTEPH and IPAH in oxygen uptake upon maximal exercise (table 3), and tidal volume at rest and at maximal exercise (0.7 (0.4-1.3) versus 0.7 (0.5-1.4) and 1.9 (0.7-2.3) versus 1.9 (1.3-3.1) L, respectively).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ventilation was slightly increased in CTEPH at rest and during exercise (15 (4-21) versus 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and 58 (29-78) versus 50 (29-82) L?min -1 ), but with no significant difference between the two groups. There were no significant differences between CTEPH and IPAH in oxygen uptake upon maximal exercise (table 3), and tidal volume at rest and at maximal exercise (0.7 (0.4-1.3) versus 0.7 (0.5-1.4) and 1.9 (0.7-2.3) versus 1.9 (1.3-3.1) L, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…Ventilatory inefficiency in PAH and CTEPH is associated with hyperventilation. This may be due to increased chemosensitivity [18] or an augmented dead space fraction [19]. ZHAI et al [19] investigated ventilatory efficiency by comparing physiological dead space fraction and EQCO 2 in PAH and CTEPH patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that these systems are activated in right HF as well (202). For example, it has been observed that plasma epinephrine levels were elevated, beta-1 adrenergic receptors were "downregulated" in RV and heart rate variation was reduced in right HF (203)(204)(205)(206). There are also trials demonstrating that RAAS is similarly activated (207,208).…”
Section: Do Beta-blockers or Digoxin Affect Ph Associated With Left Hmentioning
confidence: 93%
“…It has been shown that, as in left heart disease, patients with PAH have altered autonomic nervous system activity, the degree of which may reflect disease severity [152]. Such abnormalities may be visible in heart rate response during recovery from exercise and readily measured in variables such as HRR1, which is the fall in HR during the first minute of recovery.…”
Section: Field Exercise Testsmentioning
confidence: 99%